Analisis Kelayakan Multimedia Fisika Interaktif Berbasis Etno-Inquiry Melalui Permainan Gopa pada Materi Gerak Parabola - Nurjumiati; Syahriani Yulianci; Nurhairunnisah; Surya Ningsyih (Jurnal Pendidikan dan Pengajaran, 2026)
The problem addressed in this study is the limited availability of physics learning media integrated with local culture, particularly the Gopa traditional game, in explaining projectile motion contextually, as well as the absence of feasibility analysis for ethno-inquiry-based multimedia. In addition, the lack of a comprehensive feasibility analysis of interactive multimedia based on ethno-inquiry has resulted in its potential use in learning not being empirically tested. This study aims to analyze the feasibility of ethno-inquiry-based interactive physics multimedia through the Gopa traditional game and to evaluate students’ responses to its implementation. This research employed a Research and Development (R&D) method adapted from the Borg and Gall model. The subjects of the study were 10 eleventh-grade high school students. Data were collected through validation questionnaires and student response questionnaires using a Likert scale (1–5), then analyzed quantitatively using percentage analysis and descriptively. The results showed that the developed multimedia was categorized as highly feasible in terms of both media and material aspects and received positive responses from students because it was considered interesting, easy to use, and helpful in understanding projectile motion concepts. Therefore, the ethno-inquiry-based interactive multimedia through the Gopa traditional game is considered feasible as an alternative contextual and local culture-based physics learning medium. The implications of this study indicate that the integration of the ethno-inquiry approach and local wisdom has the potential to strengthen students’ conceptual understanding, numeracy literacy, and cultural literacy in physics learning.